2018
DOI: 10.1186/s40100-018-0117-1
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ willingness to pay for natural food: evidence from an artefactual field experiment

Abstract: Among foods with credence attributes, food with "natural" components have received in the last years particular attention by consumers. This study applies the BDM incentive compatible mechanism to explore young (18-35 years old) consumers' interest and willingness to pay for chewing gums having the natural attribute. Our analysis shows that over 68% of consumers are interested in the natural attribute and are willing to pay a price premium. We also find that consumers' higher age and interest in the environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 48 publications
0
11
0
1
Order By: Relevance
“…The descriptive analyzes of the sample are summarized in Table 1. 5 3.80 0.77 1 5 Monthly income 6 1.81 0.…”
Section: Socio-demographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The descriptive analyzes of the sample are summarized in Table 1. 5 3.80 0.77 1 5 Monthly income 6 1.81 0.…”
Section: Socio-demographic Characteristicsmentioning
confidence: 99%
“…In this regard, over the years, changes in consumer behavior have been observed, with increasing number of individuals choosing more sustainable products in their daily dietary choice [4]. This is due to the spreading awareness of environmental impacts of the agri-food sector [5], as well as the growing interest for the health dimension of food related to nutrients intake [6] and food safety [7].…”
Section: Introductionmentioning
confidence: 99%
“…The widespread use of the term, even without a universal definition, suggests that it provides an advantage from the perspective of marketing and sales of products and services. Indeed, research has shown that people are willing to pay a premium for natural items (Migliore, Borrello, Lombardi, & Schifani, ).…”
Section: Introductionmentioning
confidence: 99%
“…They interpret the food naturalness as an indicator of the healthiness and quality of the product, derived from the 'integral integrity of the product' [17]. As a result, natural products are perceived as good for your health as they are free of additives and other synthetic substances, perceived to reduce the healthiness of food [18][19][20][21]. Furthermore, the idea of natural eating seems to generate a perception of physical and emotional well-being [22].…”
Section: Theoretical Frameworkmentioning
confidence: 99%